2013
DOI: 10.1111/imr.12115
|View full text |Cite
|
Sign up to set email alerts
|

Cofilin: a redox sensitive mediator of actin dynamics during T‐cell activation and migration

Abstract: Cofilin is an actin-binding protein that depolymerizes and/or severs actin filaments. This dual function of cofilin makes it one of the major regulators of actin dynamics important for T-cell activation and migration. The activity of cofilin is spatio-temporally regulated. Its main control mechanisms comprise a molecular toolbox of phospho-, phospholipid, and redox regulation. Phosphorylated cofilin is inactive and represents the dominant cofilin fraction in the cytoplasm of resting human T cells. A fraction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 179 publications
(270 reference statements)
4
71
0
Order By: Relevance
“…The protein cofilin, which regulates the actin filament system in dendrites and spines, has been shown to be redox-sensitive (Samstag et al 2013), and cofilin and its regulatory network have recently been shown to be highly responsive to irradiation (cf. below, ).…”
Section: Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein cofilin, which regulates the actin filament system in dendrites and spines, has been shown to be redox-sensitive (Samstag et al 2013), and cofilin and its regulatory network have recently been shown to be highly responsive to irradiation (cf. below, ).…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Notably, cofilin organizes surface receptor complexes in the "immunological synapse". Its activity may polymerize or depolymerize actin depending on the availability of G-actin, and cofilin activity is under direct redox control, which implicates it in oxidative disturbances of actin dynamics (Samstag et al 2013). This may render it acutely sensitive to radiation or to persistent oxidative stress.…”
Section: F Neuronal and Brain Tissue Structural Changesmentioning
confidence: 99%
“…Evidence indicates that ROS generated by the myeloperoxidase-hydrogen peroxide system could lead to a suppression of T cells. Suppression (52)(53)(54) or induced apoptosis (55) of T cells by an oxidative environment have been described recently. Additionally, studies showed that MPO, or its products, could modulate the initiation of the T cell response via suppression of dendritic cells (36,56).…”
Section: Role Of Myeloperoxidase In Malaria Infectionmentioning
confidence: 99%
“…Moreover, myosin cysteins are susceptible to S-glutathionylation modulating its ATPase activity [91]. Cofilin controls stability of F-actin and, depending on its oxidation state, actin dynamics are impaired [92].…”
Section: Redox Modifications and Regulation Of Actinmentioning
confidence: 99%
“…Cofilin activity can be regulated via reactive oxygen species through redox-sensitive proteins and signalling cascades, including the activities of RhoA [98], PKD1 [99], and 14-3-3 zeta [100]. Moreover, redox regulation of specific cysteine residues of cofilin is emerging as another form of post-translational regulation, also assuring rapid and spatial control of protein function and cytoskeleton action towards distinct stimuli [92]. The human, non-muscle isoform cofilin-1 contains four cysteine residues at the positions 39, 80, 139 and 147; with 39 and 80 being located inside the protein and 139 and 147 being located on the surface of the protein [101].…”
Section: Redox Regulation Of Cofilin Activitymentioning
confidence: 99%